1995
DOI: 10.1038/hdy.1995.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inbreeding on autogamy in Phlox

Abstract: The effect of inbreeding on autogamy was studied in two greenhouse-grown populations of the weakly self-compatible Phlox drummondii. Sixty-one plants from a Lytle, TX. population and 20 plants from a Bastrop, TX. population were self-fertilized to generate an equivalent number of 10-plant self families. The mean level of autogamy in the Lytle progeny was 2.49 per cent vs. 1.03 per cent in their parents. The mean level of autogamy in the Bastrop progeny was 13.35 per cent vs.5.95 per cent in their parents. Auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…solstitialis populations that contain individuals that are partially self-compatible were identified in our study and in other studies (Harrod and Taylor 1995, Maddox et al 1996, Sun and Ritland 1998. Recent findings indicate that small levels of self-compatibility in predominantly self-incompatible species may be increased by environmental stress and inbreeding (Levin 1995, Hiscock 2000. Strong selection for self-compatibility in C. solstitialis may result in satellite populations sustained by higher rates of self-compatibility than exist in larger core populations.…”
Section: Breeding Systems and Invasivenesssupporting
confidence: 74%
“…solstitialis populations that contain individuals that are partially self-compatible were identified in our study and in other studies (Harrod and Taylor 1995, Maddox et al 1996, Sun and Ritland 1998. Recent findings indicate that small levels of self-compatibility in predominantly self-incompatible species may be increased by environmental stress and inbreeding (Levin 1995, Hiscock 2000. Strong selection for self-compatibility in C. solstitialis may result in satellite populations sustained by higher rates of self-compatibility than exist in larger core populations.…”
Section: Breeding Systems and Invasivenesssupporting
confidence: 74%
“…Self-fertility in weak SI families increased slightly in day-1 flowers and decreased slightly in day-4 flowers, but individual families differed greatly in their response to inbreeding. This suggests that self-fertility can respond in various ways to inbreeding, concordant with other studies that have found both increases (Robacker and Ascher, 1978;Dana and Ascher, 1985;Levin, 1995) and decreases (Wilsie, 1958;Krebs and Hancock, 1990) in self-fertility in response to inbreeding in partially SI species. The tendency for weak SI families to decline in self-fertility with inbreeding, combined with high overall levels of inbreeding depression, show that it is unlikely the species could become highly selffertile or even practice repeated generations of self-fertilization.…”
Section: Discussionsupporting
confidence: 91%
“…A reduction in heterozygosity per se may increase the penchant for selfing in predominantly outcrossing plants. Increased selfing following inbreeding has been demonstrated in Secale cereale (Lundquist, 1960), Agrostis tenuis (Antonovics, 1968), Nemesia strumosa (Henny and Ascher, 1976), Petunia integrifolia (Dana and Ascher, 1985), Senecio squalidus (Hiscock, 2000), Solanum caroliniense (Mena-Ali et al, 2008) and in Phlox drummondii (Levin, 1995).…”
Section: Increased Selfing Due To Inadequate Pollen Receiptmentioning
confidence: 99%